Keausan Yang Terjadi Pada Kampas Ganda Akibat Adanya Gesekan Dengan Clutch Cover (Matahari Kopling) Pada Forklift Di PT. ABC - Darmadi, Herry; RAHMADI, DWI; Sidabutar, Naqasya Asyrori (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2025)
Forklift is one of the means of transportation used in PT ABC. PT ABC is the first company to produce fish oil and flour using whole fish as raw material. Wear on engine components is a problem that is often faced in industry, especially in heavy equipment such as forklifts. One component that experiences significant wear is the double clutch, which functions as a connection between the engine and transmission in the clutch system. One of the main causes of wear on the double clutch is friction that occurs with the clutch cover (clutch sun). This study aims to determine the amount of wear volume that occurs on the double clutch and to determine the amount of wear rate that occurs on the double clutch. The method used in this study is data analysis. From the results of the study, it can be concluded that the Wear Volume that occurs on the double clutch is 7.1053 x 10-4 mm3 and the Wear Rate that occurs on the double clutch is 2.13624343 x 10-18 g / sec.mm2.